Mother's Perception of Children's Motor Development in Southern Brazil. Issue 1 (February 2017) - Silva, Sabrine D.; Flôres, Fábio S.; Corrêa, Shaiane L.; Cordovil, Rita; Copetti, Fernando
Parents' perceptions of children's motor competence are important because they influence the way parents interact with their children to promote motor skills development. Thirty-six mothers of 16- to 66-month old children (61%, 22 boys and 39%, 14 girls, n  = 36) estimated their child's performance while the child was being evaluated, by another trained researcher, with the same scale (Peabody Developmental Motor Scale 2nd Ed.) in a different room. Underestimations, accurate estimations, overestimations, and parental accuracy were investigated. Mothers overestimated significantly their child's stationary and locomotion skills and their GMQ and Total Motor Quotients (TMQ). Identical levels of motor performance were found in girls and boys, and estimation accuracy was similar for both genders. We discuss our results in the context of the parents' routines (little time interacting with children actively) and the relevance of their perceptions of the children's abilities as a further influence on the children's development and engagement in physical activities.